Evaluation of selected echinoderms from peninsular Malaysia for cytotoxicity against HepG2 cells, antioxidant and antibacterial activities, and their metabolites profiling - Yosie Andriani, Nurul Hazirah Mat Lazim & , Asnuzilawati Asari, Faridah Mohamad, Tengku Sifzizul Tengku Muhammad, Noraznawati Ismail & , Mariam Taib, Hermansyah Amir, Aziz Ahmad, Habsah Mohamad (Journal of Applied Pharmaceutical Science, 2018)
Study on the evaluation of Acanthaster planci, Echinaster luzonicus, and Echinothrix calamaris from Peninsular Malaysia for cytotoxicity against human hepatocellular liver carcinoma cells (HepG2), antioxidant and antibacterial activities were evaluated on their methanol extracts. The cytotoxicity, antioxidant and antibacterial activities were conducted by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4sulfophenyl)-2H-tetrazolium assay, 1,1-diphenyl-2-picryl hydrazyl free radical scavenging assay, and disc diffusion method, respectively. In addition, thin layer chromatography (TLC) was done to profile the metabolites within the extracts using Dragendorff’s reagent to identify the presence of alkaloids metabolite. The cytotoxicity result showed that the treatment of the extracts (100 mg/ml) inhibited the proliferation of HepG2 cells and the IC50 for all extracts exceeded 30 mg/ml indicating that the extracts were not cytotoxic to the cells. For antioxidant activity, all extracts showed good antioxidant activity with the IC50 value obtained more than 50%. While, screening of bacterial properties using Gram-positive bacteria strains (Staphylococcus aureus, Bacillus cereus, and Micrococcus sp.) and Gram-negative bacteria strains (Escherichia coli, Salmonella typhimurium, and Pseudomonas aeruginosa) showed that all samples have antibacterial activity against Micrococcus sp. only. The TLC profiling of A. planci and E. luzonicus showed the presence of alkaloids. Since the result found that A. planci, E. luzonicus, and E. calamaris have no cytotoxic activity against HepG2 cells (no IC50 value), further study such as anti-atherosclerosis potential agent can be evaluated. Subsequently, a very good antioxidant activity of all samples is also good to screen their potency as an anticancer agent against some cancer cells.
Keywords: Acanthaster planci, Echinaster luzonicus, Echinothrix calamaris, cytotoxicity, antibacterial, antioxidant.